Building up prestasi belajar siswa dengan media inovatif - Anwar Sewang (Indonesian Journal of Educational Science (IJES), 2021)
This study aims to determine the effectiveness of using image media in learning citizenship education at SMAN 4 Polewali, Polewali Mandar Regency. This type of research is experimental research with inferential statistical analysis using t-test technique. The population in this study were students of class X SMAN 4 Polewali totaling 70 students with a total sampling technique. Data retrieval is done through documentation and test techniques. The results showed that there were differences in student achievement using picture media and those not using picture media, with the experimental group's average student achievement being 80.35 while the control group's student achievement was an average of 60.95.